Pengetahuan Masyarakat tentang Penggunaan Sistem Penanggulangan Gawat Darurat Terpadu - Febrian Trinugraha; Kartinah Kartinah (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the public knowledge level about using the Integrated Emergency Management System (SPGDT) in Surakarta City in general terms and by category. The research method used is quantitative research using a descriptive design. The results showed that 77 respondents needed more knowledge about the integrated emergency management system in Surakarta City; this could be due to the low level of response education, which affected their ability. Most respondents who know about the SPGDT are female, of productive age (20-53 years), with an undergraduate degree (S1). In conclusion, most people in Surakarta City need to learn about the importance and benefits of the Surakarta City Integrated Emergency Management System. Keywords: Call Center, Emergency, Knowledge, SPGDT